Effectiveness of (Ki-67) a Cell Proliferative Marker for Distinguishing Overlapping Skin Lesions - Hala N. Al Salman; Qasim S. Al Chalabi; Anfal L. Al Harbawi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: it has been always a challenge to differentiate keratoacanthoma (KA) from squamous cellcarcinoma (SCC) and trichoepithelioma (TE) from Basal Cell Carcinoma (BCC). K-i67, a nuclear marker, isa protein whose expression is strictly related to cell proliferation. Therefore, this can be used as an excellentproliferative marker to differentiate between benign and malignant skin lesions.Aim of the Current Study: this study was conducted to investigate the quantitative differences in nuclearexpression of the proliferative index (Ki-67) in SCC, KA, BCC and TE.Materials and Methods: A cross-sectional study enrolling 65 patients selected from private dermatologicaloutpatients clinics at Ibn-Sina Teaching Hospital, Mosul, Iraq diagnosed clinically by dermatologists asBCC, SCC, KA, and TE during the period from Jan 2019- Jan 2020. Their biopsies were sent for routinehistopathological study and additional Immunohistochemical staining using a Ki-67 marker.Results: Ki- 67 expression was seen in all cases ranging in intensity between 3-70%. Moderate expressionwas noticed in (79%) of BCC cases whereas (43%) of well-differentiated SCC cases had mild expression.Quite the reverse, the intensity of Ki-67 immunostaining ranged from 1-20% and 1-5% in KA and TErespectively.Conclusion: Ki-67 can be used as a significant biological marker to differentiate between benignity andmalignancy of overlapping